Analisis Peningkatan Faktor Keamanan Lereng Pada Areal Bekas Tambang Pasir Dan Batu di Desa Ngablak, Kecamatan Cluwak, Kabupaten Pati - Rinal Khaidar Ali; Najib Najib; Ahmad Nasrudin (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2017)
Management of post mining land become serious concern for government in current time. Post miningarea that located in Ngablak village, Cluwak districts of Pati is one of post mining areas that did notmanaged and creates problems to civilian and village government, for example are safety andenvironment problems. Safety of environment disturbed because of mining activities that finished andcreated unstable slope (potentially landslide) caused by land dredging. To solve this problems,government need to make some research about stability of slope and studies about method ofanalysis which can increase the safety factor of slope. Slope stability analysis can be done with Side6.0 software which needs laboratory result data of soil mechanics. Methods that can increase slope’ssafety factor can be installation of retaining wall and cut and fill method that make the slope becometerraces. Efficiency of method that will be selected, can be tested by using Slide 6.0 software.Installation of retaining wall could increase the safety factor’s value become 1.103, this valuerepresents that the slope is still potentially to be landslide. However, cut and fill can increases safetyfactor’s value become 1.330, that representing slope condition is stable and safe.